PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS PROBLEM SOLVING PADA MATERI KEBERAGAMAN DAN TOLERANSI DALAM PEMBELAJARAN PKN SMP - Azahwa Ramadhani; Darmansyah; Alkadri Masnur; Khairul Alfahani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a problem-solving-based educational game on diversity and tolerance material in Civic Education (PKN) for eighth-grade junior high school students. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 22 students of grade VIII at SMP IT Amanah Sungai Penuh. Data were collected through validation questionnaires, practicality questionnaires, and learning outcome tests in the form of pretest and posttest. The product developed is an interactive educational game created using Articulate Storyline, designed with problem-based scenarios to encourage students’ critical thinking and active participation in learning. The validation results showed that the media achieved a very high level of validity, with an average score of 4.70 for material aspects and 4.82 for media aspects. The practicality test indicated an average score of 4.51, categorized as very practical, showing that the media is easy to use and engaging for students. Furthermore, the effectiveness test revealed an N-Gain score of 72.80%, which falls into the moderately effective category, indicating a significant improvement in students’ learning outcomes. In conclusion, the developed problem-solving-based educational game using Articulate Storyline is valid, practical, and effective in improving students’ learning outcomes in Civic Education, particularly on diversity and tolerance material.